(untitled) (Journal of Science and Technology, 2016)
The roasting conditions for gold ore flotation concentrate from two sources have been studied. Temperatures from 450 to 850°C were employed for one-stage roasting in air for 6 hours. Two-stage roasting was also carried out employing 550°C followed by 750°C for a total time of 2, 4, and 6 hours. The surface areas of the calcines were measured using the B.E.T. nitrogen adsorption technique; the calcine were then leached for gold in 0.1% NaCN solution over a 24 hour period. Results showed that for the one-stage process gold extraction was maximum at 650-700°C for both sample A and B respectively. The surface area was found to decrease with increasing roasting temperature and this was believed to be the cause of the low gold extraction obtained above 700°C. At the lower temperatures below 650°C the low extraction was ascribed to the presence of uneliminated C, S. and As. Two-stage roasting of sample B for 6 hours yielded calcines with higher surface area and consequently a higher gold extraction.